2013
DOI: 10.1186/1477-7819-11-139
|View full text |Cite
|
Sign up to set email alerts
|

Pure mucinous carcinoma of the breast: clinicopathologic characteristics and long-term outcome among Taiwanese women

Abstract: BackgroundPure mucinous carcinoma (MC) is found in about 3.5% of all newly diagnosed breast cancer patients in Taiwan. MC is a relatively rare malignancy of breast cancer, and its nature, behaviors, treatment pattern and long-term follow-up are not well understood. The study aimed to investigate the incidence rate, treatment patterns, and prognostic factors of MC of the breast and the clinical long-term outcomes compared with infiltrating ductal carcinoma not otherwise specified (IDC) in the middle and south T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 18 publications
(25 reference statements)
5
36
2
Order By: Relevance
“…The patient's cancer was, however, HER2 positive and grade 3, with nodal involvement, which are uncommon characteristics of both, pure as well as mixed mucinous carcinomas 9 10. We found only a single case report of a HER2 positive mucinous carcinoma in the literature,11 and eight HER2 positive cases from a retrospective series of 93 pure mucinous carcinomas in Taiwanese women 12. Nodal involvement is rare, even with large primary pure or mixed mucinous tumours (WHO) 4.…”
Section: Discussionmentioning
confidence: 76%
“…The patient's cancer was, however, HER2 positive and grade 3, with nodal involvement, which are uncommon characteristics of both, pure as well as mixed mucinous carcinomas 9 10. We found only a single case report of a HER2 positive mucinous carcinoma in the literature,11 and eight HER2 positive cases from a retrospective series of 93 pure mucinous carcinomas in Taiwanese women 12. Nodal involvement is rare, even with large primary pure or mixed mucinous tumours (WHO) 4.…”
Section: Discussionmentioning
confidence: 76%
“…MC also has a higher rate of oestrogen receptor (ER) expression (73-94% versus 26-82%, supplementary material, Figure S5) and is associated with more progesterone receptor (PR) expression (63-90% versus 47-74%, supplementary material, Figure S6) [137][138][139][140][146][147][148][149][150][151]. For MC, less HER-2 overexpression has been reported compared with NMC (0-14% versus 20-41%, supplementary material, Figure S7) [139,140,146,147,[149][150][151]. Studies that included small numbers of MC demonstrated that mutated PIK3CA, which is found in 16-33% of IDCs, is not a common finding in MC (0-13%), supplementary material, Figure S8 [125,[152][153][154][155][156][157].…”
Section: Mucinous Breast Carcinomamentioning
confidence: 99%
“…MC of the breast is associated with higher rates of MUC2 expression than IDC [98,145]. MC also has a higher rate of oestrogen receptor (ER) expression (73-94% versus 26-82%, supplementary material, Figure S5) and is associated with more progesterone receptor (PR) expression (63-90% versus 47-74%, supplementary material, Figure S6) [137][138][139][140][146][147][148][149][150][151]. For MC, less HER-2 overexpression has been reported compared with NMC (0-14% versus 20-41%, supplementary material, Figure S7) [139,140,146,147,[149][150][151].…”
Section: Mucinous Breast Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of previous MBC clinical studies found that MBC showed higher ER-and PR-positive rates, less lymph node metastasis, lower TNM stage and notably higher OS and DFS rates (16)(17)(18)(19)(20). The present study analyzed the basic information of MBC patients and compared it with that from IDC-NOS patients treated in the same period.…”
Section: Discussionmentioning
confidence: 99%